2020
DOI: 10.1155/2020/1294151
|View full text |Cite
|
Sign up to set email alerts
|

The Separation of Antler Polypeptide and Its Effects on the Proliferation and Osteogenetic Differentiation of Bone Marrow Mesenchymal Stem Cells

Abstract: Background. Colla Cornus Cervi (CCC) has been used as a traditional Chinese medicine in the treatment of osteoporosis and osteonecrosis of the femoral head. However, the bioavailability of CCC is seriously limited owing to its large molecular weight and complex ingredients. In the present study, antler polypeptide was separated from CCC, and the effects of antler polypeptide on rat bone marrow mesenchymal stem cells (BMSCs) were investigated. Methods. Antler polypeptide was separated from Colla Cornus Cervi by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The polypeptide content was determined by the biuret method 24 . One milliliter of sample solution was mixed with 1 mL of Trichloroacetic acid (TCA) solution (100 g L −1 ) and kept at room temperature for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polypeptide content was determined by the biuret method 24 . One milliliter of sample solution was mixed with 1 mL of Trichloroacetic acid (TCA) solution (100 g L −1 ) and kept at room temperature for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The polypeptide content was determined by the biuret method. 24 One milliliter of sample solution was mixed with 1 mL of Trichloroacetic acid (TCA) solution (100 g L −1 ) and kept at room temperature for 30 min. After centrifugation, 1 mL of the supernatant and 4 mL of the biuret reagent (0.375 g CuSO 4 25 The gradient elution procedure is given in Table 1.…”
Section: Polypeptide and Amino Acid Content Analysismentioning
confidence: 99%
“…Previous studies (5,6) have stated that CHRM can play a positive role in this disease, but its speci c pharmacological effects have not been elucidated.…”
Section: Introductionmentioning
confidence: 97%
“…The sika deer antler preparation has been used to strengthen bones and muscles, promote blood flow, reduce chronic joint pain, lower cholesterol levels, increase immune function, and have a positive impact on antioxidant capacity. Studies have shown that sika deer antler may have preventive and therapeutic effects on femoral head necrosis, and may also help to produce sperm and strengthen bones (Pu & Peng, 2018 ; Wang et al, 2020 ). Pilose antlers may be used as a source of calcium to treat bone degeneration and strengthen bone (Chen et al, 2019 ; Chu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%